Performance test and emission characteristics of diesel engine with alternate fuel blends and nano additives. Issue 7 (19th May 2021) - Yogaraj, D.; Mohamed Iqbal, S.; Gokulakrishna, R.; Meikandan, M.
ABSTRACT: Nowadays, the use of petroleum products in vehicles is both costly and hazardous to the environment. The world is looking for alternate fuels to fulfil their transportation needs. In this project, usage of jatropha biodiesel in CI engine is investigated. A blend consisting of biodiesel and silver-doped titanium dioxide (Ag-TiO2 ) is prepared. After preparing the blend, the performance and emission characteristics of a diesel engine with the blend were compared. Addition of the additives leads to complete combustion which leads to lower brake-specific fuel consumption and lower carbon dioxide and hydrocarbon emission. However, there was higher NOx emission in all cases. The results of the experiment showed that the addition of nano additives leads to improved performance and emission of biodiesels compared to generic biodiesel.